Keep an eye out: A rare case of acute-onset Charles Bonnet Syndrome after Stanford type A aortic dissection repair surgery. Issue 2 (May 2017) - Cook, Fabian; Dougherty, Scott; Moreton, Robert; Khorsandi, Maziar
Charles Bonnet Syndrome describes the triad of complex visual hallucinations secondary to ophthalmic pathology in psychologically normal people. We present a rare case of acute-onset Charles Bonnet Syndrome following cardiac surgery that resulted in profound loss of visual acuity in both eyes with characteristic visual hallucinations that were initially mistaken for delirium. Computed tomography of the brain revealed bilateral occipital infarcts, providing the substrate for Charles Bonnet Syndrome. A high index of suspicion should be maintained in cognitively intact patients with visual loss who are also experiencing visual hallucinations to ensure prompt diagnosis and management of this often overlooked condition.